Dual energy CT in clinical practice - Johnson, Thorsten R. C. (Medical radiology : diagnostic imaging., 2011)
Dual-energy CT is a novel, rapidly emerging imaging technique which offers important new functional and specific information. With implementation of the technology in commercially available scanners, many clinical applications are now feasible. In this book, physicists and specialists from different CT manufacturers provide an insight into the technological basis of, and the different approaches to, dual-energy CT. Renowned medical scientists in the field explain the pathophysiological and molecular background of the technique, discuss its applications, provide detailed advice on how to obtain optimal results, and offer hints regarding clinical interpretation. The main focus is on the use of dual-energy CT in daily clinical practice, and individual sections are devoted to imaging of the vascular system, the thorax, the abdomen, and the extremities. Evaluations and recommendations are based on personal experience and peer-reviewed literature. Plenty of carefully chosen high-quality images are included to illustrate the clinical benefits of the technique.